Effect Of Gross Profit, Operating Profit, And Net Profit In Predicting Cash Flow In The Future Of The Company Registered Manufactures On The Indonesian Stock Exchange - Hutabarat, Metyria Imelda; Putra Ginting, Winner Aan Suranta; Sirait, Fransiska; Ginting, Wahyudi Pialanta (Cattleya Darmaya Fortuna, 2024)
This research was conducted to provide empirical evidence of the influence of gross profit, operating profit and net profit in predicting cash flow. The research population is manufacturing companies listed on the Indonesian Stock Exchange. The sampling technique used the purposive sampling method used in selecting objects as samples in this research were 57 sample companies. The analysis model used in this research is a multiple linear regression analysis model carried out with the help of the SPSS version 26 program. The results of this research show that partially gross profit, operating profit and net profit have a significant positive effect on cash flow. The research results simultaneously show that gross profit, operating profit, net profit have a significant positive influence on cash flow.